Digital Empowerment: Efektivitas Program PENA bagi UMKM Perempuan di Semarang - Via Amalia; Rusdarti Rusdarti; Inaya Sari Melati; Lola Kurnia Pitaloka (Jurnal Riptek, 2025)
This study examines the impact of the PENA Program on the digitalization of women-led MSMEs in Semarang City and its implications for empowerment and business sustainability. Using a qualitative approach with thematic analysis as the main method, data were gathered through in-depth interviews with eleven female MSME entrepreneurs participating in the PENA Program.Results show that around 73% of respondents experienced significant improvements in digital adoption, particularly in e-commerce, digital payment, and social media marketing. Three main themes emerged: (1) enhanced digital capabilities through structured mentoring, (2) empowerment through increased visibility and self-confidence, and (3) persistent challenges such as time constraints and limited infrastructure. The PENA Program effectively facilitates access to digital tools and skills development, though adaptation varies depending on digital literacy and social support.Digitalization strengthens womens empowerment by enabling participants to expand markets, manage online sales efficiently, and build entrepreneurial confidence. However, dual gender roles and uneven access to technology remain barriers. The study concludes that improving digital literacy and providing adaptive mentoring are crucial to advancing women-led MSME digital transformation, offering insights for inclusive and sustainable empowerment policies.